IMPLEMENTASI PROGRAM BANTUAN PANGAN NON TUNAI (BPNT) DI KELURAHAN REJOSARI KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Vatmawati, Mega Octavia; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Poor people are citizens who are entitled to get welfare from the government. The provision of social assistance in the form of non-cash food assistance is one of the government's efforts to prosper the poor through the distribution of non-cash social assistance using the banking system, which is expected to support the recipient's productive behavior. But until now the implementation of the assistance still received complaints from the public who were not satisfied because there were still many poor people who had never received assistance and also the slow process of distributing aid. The purpose of this study was to see how the Implementation of the Non-Cash Food Assistance Program in Rejosari Sub-District, Tenayan Raya District, Pekanbaru City. This study used descriptive qualitative method. This study uses interviews, observation, and documentation using a purposive sampling method to source information and analyze data with triangulation techniques. The results showed that the Implementation of the Non-Cash Food Assistance Program in Rejosari Sub-District, Tenayan Raya District, Pekanbaru City was still not optimal, because it was not right on target beneficiaries in the implementation and not timely disbursement of funds, so the program objectives had not been achieved properly.Keywords: Implementation, Food Aid, Public Policy